The Analisis Kemampuan Numerasi Siswa SMA Berdasarkan Hasil Laporan Pendidikan Kabupaten Pacitan : Analisis Kemampuan Numerasi Siswa SMA Berdasarkan Hasil Laporan Pendidikan Kabupaten Pacitan - Yuniarti, Dwi Ariani (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2024)
This research examines the numeracy skills of high school students in Pacitan Regency based on the 2024 education report. The analysis results indicate a significant improvement in overall numeracy scores, reaching 83.62%, which is a 22.05% increase from the previous year. Numeracy proficiency distribution shows that a majority of students (61.64%) have met or exceeded competency standards. Further analysis reveals enhancements across all mathematical competency domains, including numbers, algebra, geometry, and data. These findings reflect the effectiveness of educational strategies implemented in Pacitan Regency in enhancing students' understanding of diverse mathematical concepts. The implications of this study underscore the importance of reinforcing evidence-based educational strategies to improve mathematics education quality at the high school level. Thus, this research not only provides a comprehensive overview of students' numeracy skills in Pacitan Regency but also lays the groundwork for developing more effective educational policies in the future.